Efficacy and Safety of Crisaborole Ointment 2% in Mild to Moderate Atopic dermatitis (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Atopic dermatitis is a common chronic inflammatory skin condition. It affects upto 20% of children and 3% of atopic dermatitisults; most of them are mild to moderate in severity. There are onle a few effective topical therapeutic options available for long term use. This study was aimed to evaluate the efficacy and safety of Crisaborole ointment (2%), a new non-steroidal topical anti-inflammatory phosphodiesterase-4 (PDE4) inhibitor for the treatment of mild to moderate Atopic dermatitis.Methods: This prospective clinical trial was conducted at the Department of Dermatology & Venereology in Shaheed Suhrawardy Medical College Hospital, Dhaka, for a period of 12-months following approval of this protocol. A total of 226 patients with Mild to moderate Atopic dermatitis were included after getting informed written consent and divided into two equal groups: Crisaborole 2% ointment and placebo. Patients were followed up at 4 th, 8th and 12th weeks of intervention. However, 20 patients were lost in this trial period, and finally 103 patients in each group were analyzed as per-protocol analysis. Data were analyzed by the SPSS 26.Results: Demographic characteristics were similar across the two groups in terms of age and gender (p>0.05 in all cases). No significant difference was noted  in age of onset, family history, personal history, precipitating factors and  pre-operative ISGA score (p>0.05). Mean ISGA score of Crisaborole 2% ointment atopic dermatitis significantly decreased from baseline to 12th week follow up (2.32 vs 0.89, p